2023
DOI: 10.1097/sap.0000000000003635
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the Impact of Topical and Intravenous Tranexamic Acid Use in Breast Plastic Surgery

Abstract: Background Topical and intravenous uses of tranexamic acid (TXA) have been shown to reduce bleeding and ecchymosis in various surgical fields. However, there is a lack of data evaluating the efficacy of TXA in breast surgery. This systematic review evaluates the impact of TXA on hematoma and seroma incidence in breast plastic surgery. Methods A systematic review of the literature was performed for all studies that evaluated the use of TXA in breast surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…However, there are no standardised recommendations for TXA in aesthetic surgery. Similar to our studies, Parmeshwar et al (Parmeshwar et al 2023 ) showed a significant reduction in haematoma formation seen in patients who received TXA in any form.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, there are no standardised recommendations for TXA in aesthetic surgery. Similar to our studies, Parmeshwar et al (Parmeshwar et al 2023 ) showed a significant reduction in haematoma formation seen in patients who received TXA in any form.…”
Section: Discussionsupporting
confidence: 92%
“…Postoperative haematomas are one of the most significant bleeding complications of plastic surgery, as they may require a return to the hospital or operating room for drainage or evacuation (Gelidan et al 2023 ). TXA has been shown to reduce haematoma formation during breast surgery (Parmeshwar et al 2023 ; Weissler et al 2020 ; Rifkin et al 2023 ). Prevention of haematoma listed in the literature includes strict blood pressure control, early discontinuation of nonsteroidal anti-inflammatory drugs and aspirin, intraoperative hemostatic agents, postoperative pain and nausea management, and monitoring of dressing and drains (Bloom et al 2021 ; Chen et al 2023 ; Cason et al 2021 ; Stewart et al 2024 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 23-25 TXA has also shown promise in minimizing blood loss and hematoma formation in breast plastic surgery, with benefits from both topical and intravenous applications. 26 Additionally, a retrospective review involving 60 patients showed reduced bruising at donor sites with locally infiltrated TXA. 27 Our group's systematic review further supports TXA's blood-saving effects during liposuction and fat grafting.…”
Section: Discussionmentioning
confidence: 99%